Market and risk: stages of hiv transmission among men with homosexual behaviors. Medellín 1993-2006 (Colombia Medica, 2007)
Background: People’s different responses to HIV prevention programs have been related to collective patterns of significance that are imposed to their behaviors, and affect the success of health interventions. Objective: To understand the social conditions by which men who have sex with men (MSM) face their risks. Methodology: A qualitative study based on the symbolic interactionism was carried out in Medellín between 1993 and 2006. The places where MSM meet were identified and visited. Focus groups with key informants and 100 in-depth interviews were conducted, of which 39 of them were conducted with MSM. Results: The study identified and studied seven scenarios where MSM face the risk of HIV. In the region, homosexuality continues to be object of social stigma and MSM must create for themselves special stages, where sexual activity can be less difficult. These conditions have been exploited by the market, which perceives MSM as consumers with payment capacity, and it has generated an expansive offer of stages where MSM act out several of their fundamental needs but, at the same time, are also exposed to different risks. The scenarios are built as normative systems generated by the market whose structure is imposed to the individual behaviors, frequently restricting their capacity to be protected from the risk of infection. Conclusion: The findings illustrate the complexity of the subjective decisions involved with the personal protection and the management of the risks; and they question the paradigm of the rational consumer. On the contrary, the conjunction of the structural vulnerability and the individual vulnerability, in a context of social exclusion, conform an intricate net that should be assumed in its complexity and integrity by health policies.